Peningkatan Kapasitas Digester Untuk Kecukupan Produksi Biogas Sebagai Bahan Bakar Generator Listrik - Rudianto, Rudianto; Zulhamidi, Zulhamidi; Edwar, Ester; Pharmayeni, Pharmayeni; Ekawati, Irna; Putri, Gustiarini Rika (Politeknik ATI Padang, 2024)
The development of dairy farming in Nagari Lasi District Canduang, Agam Regency, West Sumatra Province, has provided the materials a massive source of biogas production. The number of cattle in Nagari Lasi has reached around 1000 heads, plus other livestock such as Buffaloes and Goats. The manufacture of digesters in the previous year's Community service activities was a success. It produces biogas and is used for cheese production and household supply. However, the amount of biogas produced is still tiny. To realize